EFFECT OF EXTRACURRICULAR ACTIVITIES, INTRACURRICULAR ACTIVITIES AND CULTURE OF PESANTREN ON ENHANCEMENT OF STUDENTS LEARNING ACHIEVEMENT IN PP. BAITUL ARQOM JEMBER - Noga Riza Faisol; Gatot Sugeng Purwono; Agustin HP (STIE Mandala Jember, 2019)
Pesantren (Islamic Boarding School) is one of the oldest educational systems in the archipelago (Indonesia). Classical method of a Kiai (religious leader of Moslem) as a figure and the mosque as a center of education proved to contribute knowledge and education character of the nation's children. Before modern education gives its influence, the classic, written or unwritten rules become a culture of positive direction for the santri (students of Islamic Boarding School) in it. Countless warriors and heroes in their era gave a share in the journey of this nation. Pesantren Modern is one of the evolutions of pesantren in responding to the development of the time. The principle of